OPTIMIZATION OF CULTURE AND CHARACTERIZATION METHODS OF DENTAL PULP STEM CELLS FOR REGENERATIVE APPLICATIONS IN DENTISTRY - Yulda Ningsih; Depi Lusianti (Journal of Stem Cell Research and Tissue Engineering, 2026)
Dental pulp stem cells (DPSCs) are a type of mesenchymal stem cell with high potential in the field of regenerative dentistry. Their successful application is greatly influenced by the methods used for isolation, culture, and characterization; however, to date, there is no fully agreed-upon standard. This article aims to review and optimize the methods of isolation, culture, and characterization of DPSCs based on the latest scientific literature in order to obtain the most effective and consistent approach for laboratory and regenerative application. This article is a methodological paper based on a literature review (2020–2025) from PubMed and Google Scholar. The protocol was developed through the synthesis of various studies related to enzymatic isolation and the explant method, cell culture using DMEM or α-MEM media, and characterization using flow cytometry and immunocytochemistry. The analysis was conducted descriptively and narratively to compare the effectiveness of each method. The enzymatic method demonstrates higher efficiency in cell isolation, whereas the explant method provides more stable cell viability. Cell culture using media supplemented with fetal bovine serum (FBS) under conditions of 37°C and 5% CO₂ supports optimal proliferation. Characterization using markers CD73, CD90, and CD105 (positive), as well as CD34 and CD45 (negative), constitutes the primary standard for DPSC identification. The combination of enzymatic isolation methods, controlled culture using standard media, and characterization based on flow cytometry represents the most optimal approach for producing high-quality DPSCs for regenerative dentistry applications.